2000
DOI: 10.1177/109861110000300405
|View full text |Cite
|
Sign up to set email alerts
|

Stress and Coping in Police Officers

Abstract: Police officers encounter numerous stressors as part of their professional duties. Dissociation, the splitting off from awareness thoughts, feelings, or memories of stressful events, is one psychological defense associated with avoidance of emotionally painful material. In this study, dissociation, stressful or traumatic experiences, and psychological adjustment were measured in a sample of police officers. Stress was not directly associated with psychological adjustment, but increased stress did predict incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 11 publications
0
33
0
1
Order By: Relevance
“…This is somewhat surprising since in the analysis coping strategies was seen as a confounder and is related to lower EE as well as DP. Considerable attention has been given to how officers cope with stress (Leonard and Alison 1999; Aaron 2000). Unlike such studies which did not present a clear conceptual definition of coping, our study benefits from a well-accepted definition of coping based on cognitive theory of stress and coping (Lazarus and Folkman 1984).…”
Section: Discussionmentioning
confidence: 93%
“…This is somewhat surprising since in the analysis coping strategies was seen as a confounder and is related to lower EE as well as DP. Considerable attention has been given to how officers cope with stress (Leonard and Alison 1999; Aaron 2000). Unlike such studies which did not present a clear conceptual definition of coping, our study benefits from a well-accepted definition of coping based on cognitive theory of stress and coping (Lazarus and Folkman 1984).…”
Section: Discussionmentioning
confidence: 93%
“…For example, police work includes offering protection to crime victims, but at the same time fighting the most terrible crimes; maintaining close and open public relations and discipline; it requires the provision of security and the operation of security facilities, material supplies and equipment. Police work is characterised as a demanding and stressful job (Aaron 2000). The effect of stress and the work environment on police officers has long been a topic of interest for researchers and many investigations related to mental health have confirmed that police officers are a risk group for increased psychosocial stress causing depersonalization, post traumatic stress syndrome, suicide and feelings of insufficient personal accomplishments (Backman et al 1997;McCafferty et al 1990;Berg et al 2006;Ward et al 2006).…”
Section: Introductionmentioning
confidence: 97%
“…The nature of police work from a personality perspective implies working in a variety of situations which demand a high capacity for stress tolerance (Aaron 2000). For example, police work includes offering protection to crime victims, but at the same time fighting the most terrible crimes; maintaining close and open public relations and discipline; it requires the provision of security and the operation of security facilities, material supplies and equipment.…”
Section: Introductionmentioning
confidence: 99%
“…Working on cases involving traumatic scenes for crimes such as child abuse, homicides, assaults, and domestic violence can be extremely difficult witness; conversely, police commonly visit the scenes of drownings, suicides, and vehicular accidents. Violence, whether intentional, self-inflicted, or accidental, are par-forthe-course in modern law enforcement work (Aaron, 2000).…”
Section: Introductionmentioning
confidence: 99%